Therapeutic Potential Of Foeniculum vulgare Mill. Derived Selenium Nanoparticles In Arthritic Balb/c Mice - Arif A (Dove Medical Press, 2019)
Ammara Arif, Attya Bhatti, Peter John Atta-Ur-Rahman School of Applied Biosciences, National University of Sciences and Technology, Islamabad, PakistanCorrespondence: Attya BhattiAtta-ur-Rahman School of Applied Biosciences, National University of Sciences and Technology, H-12, Islamabad, PakistanTel +92 51 90856128Fax +92 51 90856102Email attyabhatti@gmail.comPurpose: Rheumatoid arthritis is an inflammatory autoimmune multifactorial disorder that primarily affects the joints. Currently available treatment options, although effective, still present some side effects. This study proposes an alternative treatment option for rheumatoid arthritis through elucidation of therapeutic potential of Foeniculum vulgare Mill.-derived selenium nanoparticles in arthritic Balb/c mice.Methods: Synthesis and characterization of selenium nanoparticles were followed by their toxicity analysis on healthy mice. Subsequently, anti-arthritic efficacy of two doses (5 mg/kg and 10 mg/kg) of synthesized selenium nanoparticles was checked on arthritic mice using multiple parameters.Results: Selenium nanoparticles in 10 mg/kg dose turned out to be more effective in treatment of rheumatoid arthritis as evident by significant reduction in paw volume and normal clinical chemistry parameters of treated arthritic mice. This dose also showed significant antioxidant activity in 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay.Conclusion: Foeniculum vulgare Mill.-derived selenium nanoparticles retain significant anti-arthritic and antioxidant potential and consequently can further be explored as an alternative treatment option for rheumatoid arthritis.Keywords: rheumatoid arthritis, nanotherapy, selenium deficiency, plant seed extract, Balb/c mice